Gigantic vortical differential scattering as a monochromatic probe for multiscale chiral structures - Ni, Jincheng (Proc Natl Acad Sci U S A, 2021)
Spin angular momentum of light is vital to investigate enantiomers characterized by circular dichroism (CD), widely adopted in biology, chemistry, and material science. However, to discriminate chiral materials with multiscale features, CD spectroscopy normally requires wavelength-swept laser sources as well as wavelength-specific optical accessories. Here, we experimentally demonstrate an orbital-angular-momentum-assisted approach to yield chiroptical signals with monochromatic light. The gigantic vortical differential scattering (VDS) of ∼120% is achieved on intrinsically chiral microstructures fabricated by femtosecond laser. The VDS measurements can robustly generate chiroptical properties on microstructures with varying geometric features (e.g., diameters and helical pitches) and detect chiral molecules with high sensitivity. This VDS scheme lays a paradigm-shift pavement toward efficiently chiroptical discrimination of multiscale chiral structures with photonic orbital angular momentum. It simplifies and complements the conventional CD spectroscopy, opening possibilities for measuring weak optical chirality, especially on mesoscale chiral architectures and macromolecules.